2016
DOI: 10.1186/s40064-016-2005-z
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectively synthesis and structural confirmation of dehydrodipeptides with dehydrobutyrine

Abstract: Most of polypeptides containing α,β-dehydroamino acids have important biological activity, so exploration of synthetic method has practical significance. In this paper, dipeptides were prepared from l-threonine by protecting of c-terminal allyl acetate, and condensing reaction with a series of N-Boc amino acid. Then, treatment of dipeptides obtained with DMAP, (Boc)2O and tetramethylguanidine in the acetonitrile occured β-elimination reaction to yield stereoselectively dehydrodipeptides. Structures of dehydrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…For the parameterization of Dhb, de Miguel et al considered only the Z-isomer, while Turpin et al considered the E-isomer. Both forms are synthetized from the same precursor, threonine, and while in general the Z-isomer is more stable than the E isomer, the latter is observed in several cases, alone or together with the Z-isomer Both parameter sets do not use CMAP corrections.…”
Section: Resultsmentioning
confidence: 99%
“…For the parameterization of Dhb, de Miguel et al considered only the Z-isomer, while Turpin et al considered the E-isomer. Both forms are synthetized from the same precursor, threonine, and while in general the Z-isomer is more stable than the E isomer, the latter is observed in several cases, alone or together with the Z-isomer Both parameter sets do not use CMAP corrections.…”
Section: Resultsmentioning
confidence: 99%
“…This method is stereoselective and yields the Z -isomer of the dehydro amino acid 57 . Tian’s team used the same method to generate dehydrobutyrine one-pot from the threonine already included in the peptide sequence [ 81 ].…”
Section: Chemical Synthesismentioning
confidence: 99%
“…This method is stereoselective and yields the Z-isomer of the dehydro amino acid 57. Tian's team used the same method to generate dehydrobutyrine one-pot from the threonine already included in the peptide sequence [81]. Still with an E1cb elimination reaction, Webster et al showed that it was possible to dehydrate threonine 58 in the presence of pentafluoropyridine and K 2 CO 3 base (Figure 22) providing protected dehydrobutyrine 61 [82].…”
Section: Synthesis Of Dehydro Amino Acidsmentioning
confidence: 99%
“…Further development of parameters either for the whole lantibiotics peptide or for the Dha and Dhb residues would be of significant value. [27][28][29][30] While such a re-parametrization of the dehydroamino amino acids is beyond the scope of this paper, but our evaluation and comparison of the two parameter sets allows us already to list the issues that need to be addressed: threonine, [31][32][33] and while in general the Z-isomer is more stable than the E isomer, 34 the later is observed in several cases, alone or together with the Z-isomer. 35 2.…”
Section: Effect Of Force Field On Structural Properties and Solubilitmentioning
confidence: 99%